Attack : with a National 'Clean Throat' campaign / by A, Corbett-Smith - Corbett-Smith, Arthur, 1879-
1929-10 1929 1920s 9 pages One in five of all the deaths in England and Wales during 1928 was due, directly or indirectly, to infection through the throat. "Through this one channel of infection," says Sir George Newman, "it is known that five principal diseases are conveyed, namely, pulmonary tuberculosis, pneumonia, influenza, poliomyelitis and cerebro-spinal fever." Or, to take another angle, these respiratory diseases, including tuberculosis, came second on the list of "killers" for 1928, thus :— Total deaths. Diseases of the Heart and circulation 22.9 per cent. RESPIRATORY DISEASES 20.9 „ Cancer 12.2 „ Nervous System diseases 9.1 „ INSURED PERSONS Amongst State-insured persons in 500 representative areas all over England and Wales it was found, in 1928, that no less than 29.64 per cent. of the total number of cases treated by panel doctors were diseases of the respiratory organs. These diseases easily headed the list. The group next in order — diseases of the digestive system — showed a percentage of 12.61 only. "Respiratory diseases form about one-fourth of all the illnesses that insurance practitioners are called upon to treat," says the Ministry of Health, "and there is no doubt that they constitute a grave menace to the health of the community." THE 'COMMON COLD' But these are figures of official record only, either of notifiable disease or of insured persons. What of the hundreds of thousands of cases which must pass unrecorded? It is estimated that the 'common cold' alone costs us £20,000,000 per annum in lost working hours and doctors' bills. The annual bill for the "common cold" works out at 5/- per head of the population. And a man with a cold in the head, let loose amongst society in tube, 'bus or office, is a dire, infective menace to everybody. Even by mere exhalation, without coughing, sneezing or speaking, that man projects bacteria into the air like a 'gas attack.' And the germs within the minute droplets of moisture may float suspended in the air for relatively long periods. The atmosphere of a closed room becomes charged with infection. In 10 out of 15 cases of the 'common cold' Dr. Rosenau found the germ of pneumonia present! 1 200/B/3/2/C693/3/13